Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Tingkat Nyeri pada Pasien Post Sectio Caesaria di Ruang Bougenvile RS Panti Wilasa Citarum - Caroline Surjadi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Sectio Caesarea delivery is an artificial delivery, through surgery where the fetus is born by making an incision in the abdominal wall and uterus with the condition that the uterus is intact and the fetus weighs above 500 grams. Surgery or surgery can cause various complaints and symptoms. The most common complaint and symptom is pain. Pain that arises as a result of surgery if not treated can have harmful effects that interfere with the healing process and will affect the growth and development process. To relieve pain in postoperative patients, nurses must teach how to relieve pain with relaxation techniques. deep breathing, deep breathing relaxation techniques are believed to be able to stimulate the body to release endogenous opoids, namely endorphins and enkephalins. Endorphins and enkephalins are substances in the body that function as inhibitors of pain transmission. Endorphins are neurotransmitters that inhibit the delivery of pain stimuli so as to reduce the sensation of pain. The decrease in pain intensity was influenced by the shift in the respondent's focus on the pain experienced on the management of deep breathing relaxation techniques so that the supply of oxygen in the tissues will increase and the brain can relax. It is the relaxed brain that will stimulate the body to produce endorphins to inhibit the transmission of pain impulses to the brain and can reduce the sensation of pain which ultimately causes the pain intensity experienced by the respondent to decrease. This type of research is descriptive in the form of a case study with a nursing care approach. The results of this study are that respondents after being given health education clients can know and apply deep breathing relaxation techniques to reduce postoperative pain.